Victorious powers and Spain in the post-war world order - Elena Kryukova (Ибероамериканские тетради)
The article deals with the foreign policy and domestic policy of Spain in the ﬁrst years after the end of the Second World War. The author analyzes the relationships between the Francoist Spain and the USA, England, France and the USSR during the difﬁcult period of entry of the country into the new system of the international relations.